DEVELOPING INTERACTIVE FLASH MEDIAFOR THEMATIC LEARNING - Dian Mustika Anggraini; Muhammad Walid (Abjadia : International Journal of Education, 2016)
This research is aimed at portraying the development of interactive flash-media to boost the young learners’ comprehension about the learning theme of energy saving that is inserted in thematic learning. Interactive media are necessary to promote different learning satisfaction for young learners. The need analysis is employed to detect the relevance of learners’ needs and appropriate material for the development of the media. By adapting the development research model by Alessi and Trollip the result of try-out material shows that the product is significantly interactive to boost learners’ comprehension. The average score of post-test is better than the pre-test X2 89.67X1 76. This interactive flash-media development is, therefore, valid, practical, and effective. هدف هذا البحث تطوير الوسائل التفاعلية بفليش لتنمية فهم الطلاب في علم الإجتماع المتكامل وخاصة بمادة توفير الطاقة وهي من التدريس الموضوعي. والوسائل التفاعلية بفليش لها فوائد في تسهيل فهم الطلاب. وقد أجرى هذا البحث تحليل الحاجات لمعرفة الارتباط بين حاجات الطلاب والوسائل السديدة لديهم. وبطريقة التطوير عند أليسسي وترولليب، عرف بأن الوسائل التفاعلية بفليش مناسبة بشخصية الطالب. ودلت نتائج التجربة على أن الوسائل المطورة متفاعلة في تنمية فهم الطلاب. وأشارت نتائج الإختبار البعدي خير من الإختبار القبلي 89,67 X2 X1 76. وأكدت مراحل البحث التطويري على أن الوسائل التفاعلية بفليش صحيحة، عملية، وفعالة في التدريس.